Awareness of shariah-compliant stock investment among students of diploma ACIS faculty, semester 5 sessions March 2019 UiTM Puncak Alam / Wan Ahmad Sidqi Wan Saifuddin - Wan Saifuddin, Wan Ahmad Sidqi (2019)
Stock investment is a monetary or capital-related activity to purchase financial instruments or other assets for profitability in the form of dividend payments, income or value-added instruments. In Malaysia, stock investing activities are divided into two types, namely Shariah-compliant stock investment and Shariah-compliant stock investment. Recognizing that there are many investors who are still investing their capital into non Shariah-compliant investments, this research is aimed to analyse the awareness of Shariah-compliant stock investment among students of diploma faculty ACIS semester 5 sessions March 2019 UiTM Puncak Alam. The design of this study is quantitatively. 74 number of students from diploma faculty ACIS UiTM Puncak Alam have been used as respondents for this research. The instrument used is a survey and set of questionnaires. Based on the set of questionnaire analysis, the understanding of the general concept of stock investment and the concept of Shariah-compliant stock investment is at moderate level of understanding. The results of this study show that the awareness of Shariah-compliant stock investment is somewhat aware level.